Kako smo Maistrovo celjsko dobo postavili v strip - Ferlež, Urh (Studia Historica Slovenica, 2025)
The article sheds light on Rudolf Maister's brief yet significant period in Celje before World War I. As the commander of the črna vojska outpost, he established connections with Slovenian intellectuals and middle school students. Under his mentorship, they published the literary journal Savinja and founded the literary society Kondor, which served as a counterpart to Ljubljana's young modernist society Zadruga. At the outbreak of World War I, they faced persecution for publishing an illegal journal. Some of the students involved were conscripted immediately after graduating from high school, and several lost their lives in the war or the struggles for the northern border. In 2024, the graphic novel Ko je Maister zaplul po Savinji was published, presenting Maister's time in Celje to young readers. The publication combines historical facts with visual storytelling, and its use in history or Slovenian language classes enables a modern approach to understanding history while achieving cross-curricular objectives, such as education for peace and multiculturalism.
Keywords: didaktika slovenščine; didaktika zgodovine; Dijaške leposlovne in znanstvene vaje Savinja; društvo Kondor; history didactics; I. gimnazija v Celju; Kondor Society; Maister, Rudolf; Slovenian language didactics